Effect of hydrogen-rich gas from char gasification on rapid pyrolysis products of low rank coal in a downer pyrolyzer. Issue 61 (30th November 2021) - Li, Ting; Li, Yong; Cheng, Yanan; Li, Xiaorong; Shen, Yanfeng; Yan, Lunjing; Wang, Meijun; Chang, Liping; Bao, Weiren
Abstract : Simulated coal gas from char gasification played a different role at different temperature (550–700 °C) during coal pyrolysis. Abstract : For guiding a novel integrated process of low-rank coal pyrolysis and gasification with char gasification gas as a heat carrier, this study investigated the effect of simulated coal gas from char gasification (SCGG) on rapid pyrolysis products of low rank coal from 550 to 700 °C in a downer pyrolyzer. Results indicated that the component of SCGG directly affected the distribution and composition of pyrolysis products. Compared with N2, SCGG facilitated the formation of tar below 600 °C. H2 in SCGG and that from water gas shift reaction (WGS: CO + H2 O → CO2 + H2 ) increased the tar yield by reacting with solid-phase free radicals in coal and inhibiting the secondary reaction of gas-phase volatile radicals. Also, CO2 in SCGG raised the tar yield due to its promotion to coal cracking. When the pyrolysis temperature exceeded 600 °C, the reforming reactions of nascent tar with steam occurred, resulting in a reduced tar yield. SCGG could distinctly reduce the coke yield (coke-S) and pitch content in tar due to the inhibiting effect of H2 from SCGG and WGS on the polycondensation reactions of volatile radicals and reforming reactions of nascent tar. The chemical composition analysis of tar by GC × GC-MS demonstrated that compared with under N2, the contents of phenols, oxygenated compounds, and heterocyclic compounds in tar under SCGG were decreased while the content of aromatics was the opposite mainly due to hydrogenation and reforming reactions of nascent tar. Also, the H/C and O/C ratios of char under the action of SCGG were higher than those under N2 at the same temperature.